Feedback for student-centered learning in two different teaching settings - Li, Yanqi; Pankratova, Stanislava (Improving University Science Teaching and Learning, 2023)
Feedback, defined as information provided regarding aspects of one’s performance or understanding, is aimed to make students learn. Learningoriented formative feedback is an important tool to increase student learning by reacting to students’ performance or understanding timely and constructively. Different teaching settings may require different ways of formative feedback to achieve student-centered learning. In this project, we apply two ways of feedback, ‘peer-feedback’ and ‘reviewing progress with students’, in two different teaching settings. These two ways of feedback are described on the website of University of Edinburgh (http://www.enhancingfeedback.ed.ac.uk/staff/resources.html). The first setting is research-based teaching with second-year master students and the second setting is theoretical lectures with heavy text book contents. We intended to investigate whether different ways of feedback can improve student learning in these two teaching settings.